Timely evaluation in international development - Webster, Jayne; Exley, Josephine; Copestake, James; Davies, Rick; Hargreaves, James (Journal of Development Effectiveness, 2018)
Impact and process evaluations are increasingly used in international development; however they are generally retrospective in outlook. A mo re timely approach to evaluation aims to identify necessary, feasible and effective changes during a programme or intervention’s lifetime. T his paper aims to identify, categorise, describe and critically apprai se methods to support more timely evaluation in international developm ent. Potential methods were identified through scoping seminar, public symposium, targeted review of the literature, and the authors’ own ex periences and opinions. Findings from the different data sources were reviewed collectively by the author group and triangulated to develop an analytical framework. We identified four purposes of timely evaluat ion for international development, and critiqued the use of approaches against four dimensions of timeliness and flexibility. Whilst we foun d significant interest in more timely approaches to evaluation in inte rnational development, there was a dearth of published empirical evide nce upon which to base strong recommendations. There is significant po tential for timely evaluation to improve international development out comes. New approaches to mixing and adapting existing methods, togethe r with new technologies offer increased potential. Research is needed to provide an empirical evidence base upon which to further develop th e application, across sectors and contexts, of timely evaluation in in ternational development.
Keywords: Adaptive learning; Outcome evaluation; Programme improvement; impact evaluation